Moss and polyaromatic hydrocarbon in Malaysia: A recent ten-year evaluation - Hanifah, Nurul Azlen; Abdullah Sani, Muhamad Shirwan; Hj. Baharuddin, Zainul Mukrim; Nik Mohd Kamil, Nik Norhazrina (IIUM Press, 2023)
The ten-year evaluation of moss species related to Polyaromatic Hydrocarbons (PAHs) in Malaysia is discussed in this paper review. Mosses are excellent biomonitors and bio-indicators of PAH deposition in the environment, often by considering the diversity and development of naturally growing bryophytes and moss bags and have been extensively used in studies of atmospheric contamination over the past decades. The review also highlighted the sources of PAHs atmospheric pollution in the environment. The sample preparation, storage, and extraction methods are discussed and reviewed. Recent applications of gas chromatography for assessing PAH compound emission by mosses are also discussed. Aside from that, current efforts to reduce PAH pollution are mentioned.